Body image and eating behavior in young adults born preterm - Matinolli, Hanna-Maria; Männistö, Satu; Sipola-Leppänen, Marika; Tikanmäki, Marjaana; Heinonen, Kati; Lahti, Jari; Lahti, Marius; Wehkalampi, Karoliina; Järvelin, Marjo-Riitta; Andersson, Sture; Lano, Aulikki; Vartia, Timo; et al. (International Journal of Eating Disorders, 2016)
Objective: Previous studies have suggested that people born preterm have increased rates of eating disorders (ED). However, a recent study suggested lower levels of ED-related symptoms in the extreme group of adults born preterm with very low birth weight (<1,500 g). We examined symptoms related to EDs in adults born early (<34 weeks of gestational age) or late (34 to <37 weeks of gestational age) preterm. Methods: We studied young adults (mean age 24.1 years) from two birth cohorts: ESTER (Northern Finland 1985–1989) and AYLS (Uusimaa, Finland, 1985–1986). Of the participants, 185 were born early preterm, 348 late preterm, and 637 were term-born controls (N = 1,170). They completed three subscales of the Eating Disorder Inventory (EDI)−2, including Drive for Thinness (DT), Body Dissatisfaction (BD), and Bulimia (B). Group differences were examined by linear regression. Results: Young women born early preterm scored 4.1 points (95% CI −8.0, −0.2, p =.04) lower in summed EDI subscale scores than women born at term, when adjusted for age and cohort. This difference was observed also in DT and BD but not for B subscales. The differences persisted after adjustments for current, pre- and neonatal characteristics. We did not observe differences in EDI scores among men or women born late preterm when compared to controls. Discussion: Women born early preterm have significantly fewer symptoms related to EDs in early adulthood when compared to their peers born at term, which may protect from developing an ED.